Dynamical, structural and chemical heterogeneities in a binary metallic glass-forming liquid. (15th March 2018) - Puosi, F; Jakse, N; Pasturel, A
Abstract: As it approaches the glass transition, particle motion in liquids becomes highly heterogeneous and regions with virtually no mobility coexist with liquid-like domains. This complex dynamic is believed to be responsible for different phenomena including non-exponential relaxation and the breakdown of the Stokes–Einstein relation. Understanding the relationships between dynamical heterogeneities and local structure in metallic liquids and glasses is a major scientific challenge. Here we use classical molecular dynamics simulations to study the atomic dynamics and microscopic structure of C u 50 Z r 50 alloy in the supercooling regime. Dynamical heterogeneities are identified via an isoconfigurational analysis. We demonstrate the transition from isolated to clustering low mobility with decreasing temperature. These slow clusters, whose sizes grow upon cooling, are also associated with concentration fluctuations, characterized by a Zr-enriched phase, with a composition C u Z r 2 . In addition, a structural analysis of slow clusters based on Voronoi tessellation evidences an increase with respect of the bulk system of the fraction of Cu atoms having a local icosahedral order. These results are in agreement with the consolidated scenario of the relevant role played by icosahedral order in the dynamic slowing-down in supercooled metal alloys.